2015
DOI: 10.1111/1365-2745.12423
|View full text |Cite
|
Sign up to set email alerts
|

Tropical montane vegetation dynamics near the upper cloud belt strongly associated with a shifting ITCZ and fire

Abstract: Summary1. Tropical montane forests house unusual and diverse biota and are considered highly vulnerable to climate change, particularly near the trade wind inversion (TWI) -the upper end of the cloud belt that defines tropical montane cloud forest (TMCF). The upper cloud belt has two possible futures: one hypothesis postulates a 'lifting cloud base', raising both the upper and lower ends of the cloud belt; the other expects the upper end of the cloud belt will change independently, with a 'shifting TWI'. 2. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…On Hispaniola, vegetation studies are most abundant for the area of the Dominican Republic ( Cano et al, 2014 ; Cano-Carmona, 2010 ; Cano-Ortiz et al, 2015 ; Durland, 1922 ; Hager and Zanoni, 1993 ; Harcourt et al, 1996 ; Liogier, 1981 ; Marcus, 2008; Martin et al, 2007 ). The natural vegetation consists of (a) dry forest ( Cano-Ortiz et al (2015) and references therein; Garcia-Fuentes, 2015), (b) mesic forest, (c) wet forest (including high elevation ‘cloud forest’ at locations where ascending air masses cause local condensation zones ( Crausbay et al, 2015 ), and low elevation ‘gallery forest’ which is periodically flooded in the study area by the Yaque River), (d) pine forest of Pinus occidentalis (endemic to Hispaniola) found from 200 to 3100 m elevation in the Cordillera Central ( Darrow and Zanoni, 1990 ; Farjon and Styles, 1997 ), (e) shrubland, and (f) herbaceous vegetation types ( Holdridge, 1945 ; Marcus et al, 2008 ). In the Ciboa Valley, only remnants of degraded natural vegetation can be found.…”
Section: Settingmentioning
confidence: 99%
“…On Hispaniola, vegetation studies are most abundant for the area of the Dominican Republic ( Cano et al, 2014 ; Cano-Carmona, 2010 ; Cano-Ortiz et al, 2015 ; Durland, 1922 ; Hager and Zanoni, 1993 ; Harcourt et al, 1996 ; Liogier, 1981 ; Marcus, 2008; Martin et al, 2007 ). The natural vegetation consists of (a) dry forest ( Cano-Ortiz et al (2015) and references therein; Garcia-Fuentes, 2015), (b) mesic forest, (c) wet forest (including high elevation ‘cloud forest’ at locations where ascending air masses cause local condensation zones ( Crausbay et al, 2015 ), and low elevation ‘gallery forest’ which is periodically flooded in the study area by the Yaque River), (d) pine forest of Pinus occidentalis (endemic to Hispaniola) found from 200 to 3100 m elevation in the Cordillera Central ( Darrow and Zanoni, 1990 ; Farjon and Styles, 1997 ), (e) shrubland, and (f) herbaceous vegetation types ( Holdridge, 1945 ; Marcus et al, 2008 ). In the Ciboa Valley, only remnants of degraded natural vegetation can be found.…”
Section: Settingmentioning
confidence: 99%
“…Recent palaeoecological studies have also demonstrated the historic importance of fire in TMFs, finding correlations in climatic fluctuations, fire occurrence and human land use over millennial time-scales (Bush et al . 2005, Conserva & Byrne 2002, Crausbay et al 2014a, 2015; Dull 2004, Hope 2009, Islebe & Hooghiemstra 1997, Urrego et al 2011). Until recently however, fire was generally considered rare in TMFs (Asbjornsen & Wickel 2009), in part because of the prominence of the fire-resistant cloud zone in the study of TMFs, but natural fires can be quite common in some parts of tropical montane landscapes (Ashton 2003, Martin & Fahey 2006, Martin et al .…”
Section: Disturbance Regimes In Tropical Montane Forestsmentioning
confidence: 99%
“…In contrast, the roles of disturbance and vegetation dynamics have received little attention in TMFs, despite the importance of these topics in understanding the spatial patterns of plant communities in other biomes and numerous palaeoecological studies distributed across the tropics that detail the pervasiveness of change and disturbance in TMF landscapes (Bush et al . 2005, Conserva & Byrne 2002, Crausbay et al 2014a, 2015; Dull 2004, Hope 2009, Islebe & Hooghiemstra 1997, Urrego et al 2011). To date, four books have provided the main synthesis and conceptual framework of TMF ecology (Bruijnzeel et al 2011, Churchill et al 1995, Hamilton et al 1995, Stadtmüller 1987), yet natural disturbances and forest dynamics received very little attention therein.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent and possibly more intense natural fires occurred around 5200 calibrated years before present (cal yr BP, where 0 yr BP corresponds to 1950 AD) in a coastal region of Puerto Rico (Caffrey andHorn 2014, Rivera-Collazo et al 2015). Regional climate issues in the pan-Caribbean area (e.g., hurricanes and the interannual changes in the position of the Intertropical Convergence Zone; Barry and Chorley 2010) were reported to induce paleofire in Dominica and Cuba (Crausbay et al 2015, Peros et al 2015. Synchrony of fire is a characteristic of climate-driven burning (Caffrey and Horn 2014).…”
Section: Introductionmentioning
confidence: 99%